2012
DOI: 10.1037/a0028332
|View full text |Cite
|
Sign up to set email alerts
|

Perceived partner support in pregnancy predicts lower maternal and infant distress.

Abstract: Maternal postpartum emotional distress is quite common and can pose significant risk to mothers and infants. The current study investigated mothers’ relationships with their partners during pregnancy and tested the hypotheses that perception of prenatal partner support is a significant predictor of changes in maternal emotional distress from midpregnancy to postpartum, and contributes to maternal ratings of infant distress to novelty. Using a prospective longitudinal design, 272 adult pregnant women were inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
207
1
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(242 citation statements)
references
References 73 publications
25
207
1
9
Order By: Relevance
“…Women with high-risk pregnancy utilize religious belief more than the risk-free group. The finding of this study that both groups use positive outlook and social support frequently is also indicated and supported by the findings of other studies (Giurgescu, et al, 2006;Gumusdal et al,2014;Lobel et al, 2002;Rini et al,2006;Stapleton et al, 2012;Yali & Lobel,2002). Moreover, the finding of this study that women with high-risk pregnancy use religious belief more as a coping strategy is supported by other studies (Giurgescu, et al, 2006;Lobel et al, 2002 ).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Women with high-risk pregnancy utilize religious belief more than the risk-free group. The finding of this study that both groups use positive outlook and social support frequently is also indicated and supported by the findings of other studies (Giurgescu, et al, 2006;Gumusdal et al,2014;Lobel et al, 2002;Rini et al,2006;Stapleton et al, 2012;Yali & Lobel,2002). Moreover, the finding of this study that women with high-risk pregnancy use religious belief more as a coping strategy is supported by other studies (Giurgescu, et al, 2006;Lobel et al, 2002 ).…”
Section: Discussionsupporting
confidence: 80%
“…"Spousal support", which is the most expressed type of support in this study, is also indicated by the results of other studies (Giurgescu, et al, 2006;Gumusdal et al,2014;Rini et al,2006;Stapleton et al, 2012). It is emphasized that anxiety levels decrease in women who perceive themselves as receiving more effective spousal support during pregnancy (Rini et al,2006), couple relationships which are supportive during pregnancy have a significant contribution to the well-being of the mother and baby (Stapleton et al, 2012), high levels of social support to women with high-risk pregnancy have a direct effect on preparation to motherhood (Giurgescu, et al,2006), pregnant women, regardless of the type of pregnancy, received the most support from their spouses (Gumusdal et al,2014).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…After the death of a child, support from a partner seems to play an important role in the recovery. Researchers proposed that subjective spousal support could provide a protective role and reduce psychological distress when encountering a traumatic event (Cox, Buhr, Owen, & Davidson, 2016; Stapleton et al, 2012). Some research also found that satisfaction with the marital relationship could encourage the healing process for bereaved parents (Lang, Gottlieb, & Amsel, 1996; Wijngaards-De Meij et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Feelings of loss of control and emotional distress not only affect the mother, but have known adverse effects for the infant as well (Stapleton et al, 2012), for instance, negative birth outcomes, poor mother-infant bonding, and long-term consequences for the child (American College of Obstetricians and Gynecologists, 2013). The early postpartum period is a crucial time to improve Scale also self-report feelings of postpartum depression?…”
mentioning
confidence: 99%